The Saint Bartholomew's Day Massacre : the Mysteries of a Crime of State. - Jouanna, Arlette (Manchester University Press, 2016)
On 18 August 1572, Paris hosted the lavish wedding of Marguerite de Valois and Henri de Navarre, which was designed to seal the reconciliation of France's Catholics and Protestants. Only six days later, the execution of the Protestant leaders on the orders of the king's council unleashed a vast massacre by Catholics of thousands of Protestants in Paris and elsewhere. Why was the celebration of concord followed so quickly by such unrestrained carnage? Arlette Jouanna's new reading of the most notorious massacre in early modern European history rejects most of the established accounts, especiall.